2024
DOI: 10.3390/s24031033
|View full text |Cite
|
Sign up to set email alerts
|

Small and Micro-Water Quality Monitoring Based on the Integration of a Full-Space Real 3D Model and IoT

Yuanrong He,
Yujie Yang,
Tingting He
et al.

Abstract: In order to address the challenges of small and micro-water pollution in parks and the low level of 3D visualization of water quality monitoring systems, this research paper proposes a novel wireless remote water quality monitoring system that combines the Internet of Things (IoT) and a 3D model of reality. To begin with, the construction of a comprehensive 3D model relies on various technologies, including unmanned aerial vehicle (UAV) tilt photography, 3D laser scanning, unmanned ship measurement, and close-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Despite the prevalent utilization of two-dimensional (2D) models, previous research has revealed several deficiencies in these models during construction activities [ 1 ]. In fact, conventional (2D) models of construction projects are now being substituted, at least partially, by a variety of digital transformations [ 2 , 3 , 4 ]. In contrast, the three-dimensional (3D) model has proven to be an effective and efficient tool to enhance the interactivity and practicality of a construction project [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the prevalent utilization of two-dimensional (2D) models, previous research has revealed several deficiencies in these models during construction activities [ 1 ]. In fact, conventional (2D) models of construction projects are now being substituted, at least partially, by a variety of digital transformations [ 2 , 3 , 4 ]. In contrast, the three-dimensional (3D) model has proven to be an effective and efficient tool to enhance the interactivity and practicality of a construction project [ 5 ].…”
Section: Introductionmentioning
confidence: 99%